3D spectroscopic measurement of argon and metal vapour in MIG welding. Issue 4 (3rd April 2018) - Kotaro, Kataoka; Kazufumi, Nomura; Kohei, mimura; Yoshinori, Hirata
ABSTRACT: Spectroscopic measurements for gas-metal arc (GMA) phenomena have been recently performed. The studies have reported that the metal vapour behaviour greatly affects the arc properties. However, they can be applied only to axially symmetric phenomena because of the assumption used for the measurement. GMA welding are normally performed with a travel speed, and most of the phenomena become axially asymmetric. This study constructed the simultaneous and multidirectional measurement system by 12 CCD cameras which can capture such axially asymmetric GMA phenomena. We measured the metal inert gas welding process with use of two types of narrowband interference filters for Ar I and Fe I during the one measurement, and observed axially asymmetrical intensity distributions in the globular and the spray transfer mode. We found that the globular transfer mode that is seemingly chaotic distribution can be regarded as the distribution where the deviation of Ar I is larger than Fe I from the axially symmetric double-ring distribution that consists of Ar I and Fe I.